Synthesis and characterisation of novel platinum (II) complexes potential chemotherapeutic drugs - Datt, Michael Steven (Rhodes University, Faculty of Science, Department of Chemistry, 2001)
The present study involves the preparation of novel mixed-ligand platinum(II) complexes in the hope of expanding the range of platinum(II) complexes that exhibit anticancer activity and which are less toxic and have a broader spectrum of activity than cisplatin and its analogues. To this end, N-(3-R-benzoyl)-N',N'-diethylthiourea, N-(3-R-benzoyl)-N'-morpholinothiourea, N-(3-Rbenzoyl)-N',N'-di(2-hydroxyethyl)thiourea (R = NO2, Cl, H, CH3, OCH3), N,N-diethyl-N'-menthyloxycarbonylthiourea and N-menthyloxycarbonyl-N'-morpholinothiourea ligands, and their corresponding mixed-ligand platinum(II) complexes of the type [PtCl(L)(RR'SO)], were synthesised and characterised by elemental analyses, IR, 1H and 195Pt NMR spectroscopy and, in some cases, X-ray crystallography. Dimethylsulfoxide complexes were prepared using all the ligands, while complexes containing unsymmetrically substituted sulfoxides were prepared using the N-benzoyl-N',N'-diethylthiourea and ,N-diethyl-'-(-)-(3R)-menthyloxycarbonylthiourea ligands only. The molecular structures of cis-(S,S)-[PtCl(DMSO)(L)] (where L = N-benzoyl-N',N'-diethylthioureato, N-(+)-(3S)-menthyloxycarbonyl-N'-morpholinothioureato), cis-(S,S)-[Pt(N-benzoyl-N',N'-diethylthioureato)Cl(MPSO)] and cis-[Pt(N-benzoyl-N',N'-diethylthioureato)2] were determined by X-ray crystallography. The X-ray crystal structure of N,N-diethyl-N'- (-)-(3R)-menthyloxycarbonylthiourea was also determined. The spectroscopic and crystallographic data are consistent with complexes containing a (S,O)-chelated ligand and a sulfur-bonded sulfoxide ligand. However, the 1H and 195Pt NMR studies showed that the alkoxycarbonylthioureato complexes exist as geometric isomers with the sulfoxide coordinated either in a cis-(S,S) or trans-(S,S) arrangement with respect to the sulfur donor atom of the chelated ligand, whereas the acylthioureato complexes yielded only cis-(S,S)-[PtCl(L)(RR'SO)] complexes. The difference in the coordination chemistry of the acylthiourea and alkoxycarbonylthiourea ligands was examined further by treatment of the [PtCl(DMSO)(L)] complexes, where L = Nbenzoyl-N',N'-diethylthioureato, N-benzoyl-N'-morpholinothioureato, N,N-diethyl-N'-(-)-(3R)- menthyloxycarbonylthioureato and N-(+)-(3S)-menthyloxycarbonyl-N'-morpholinothioureato, with PPh3 to give the corresponding [PtCl(L)(PPh3)] and [Pt(L)(PPh3)2]+ complexes. 31P NMR studies of these complexes reveal that the alkoxycarbonylthioureato ligands bind less strongly than the acylthioureato ligands, which is consistent with the crystallographic studies. The morpholine derivatives of the acylthioureato and alkoxycarbonylthioureato ligand systems also appear to bind less tightly than the diethyl derivatives. The weaker binding properties of the alkoxycarbonylthioureato ligands might be a possible explanation for the observed geometric isomerisation of these complexes, with the mechanism of isomerisation involving a chelate ringiv opening step. Furthermore, crystallographic and 31P NMR studies suggest that the acylthioureato carbonyl oxygen donor atom is relatively softer and therefore has a greater trans-influence than the carbonyl oxygen donor atom of the alkoxycarbonylthioureato ligand. The substitution kinetics of the chloride and sulfoxide leaving groups by azide, iodide, thiocyanate, triphenylphosphine, 2-mercaptobenzimidazole, 4-(dimethylamino)pyridine and thiourea, from selected cis-(S,S)-[PtCl(N,N-dialkyl-N'-(3-R-benzoyl)thioureato)(RR'SO)] complexes, in methanol, were evaluated to determine if variation of the electronic properties of the chelated ligand and variation of the sulfoxide have a significant influence on the reactivity of these complexes. Two consecutive reactions were observed. It was found that neutral nucleophiles initially substitute the dimethylsulfoxide, while anionic nucleophiles substituted the chloride ligand. For all the nucleophiles studied, the first substitution step was evaluated, except for triphenylphosphine and 4-(dimethylamino)pyridine, where the second step was also evaluated. The overall order of reactivity for the first substitution step was; N3 - < DMAP < I- < SCN- < MBI < thiourea < PPh3, with the rate varying three orders of magnitude. The substitution of the dimethylsulfoxide ligand by PPh3 from cis-(S,S)-[Pt(N-benzoyl-N',N'-diethylthioureato)Cl-(DMSO)] to form cis-(S,P)-[Pt(N-benzoyl-N',N'-diethylthioureato)Cl(PPh3)] was confirmed by X-ray crystallography. In general, manipulation of the chelating moiety, as well as interchanging the sulfoxide did not alter the reactivity of these complexes to a great extent. The anticancer activity of all the platinum(II) sulfoxide complexes were evaluated against a HeLa cell line, of which three complexes, cis-(S,S)-[PtCl(DMSO)(N,N-diethyl-N'-(3-nitrobenzoyl)- thioureato)], cis-(S,S)-[PtCl(DMSO)(N-morpholino-N'-(3-nitrorobenzoyl)thioureato)] and cis-(S,S)-[PtCl(DMSO)(N-(3-methoxybenzoyl)-N'-morpholinothioureato)] exhibited a concentration dependent anti-proliferative effect, but were less potent than cisplatin. These three complexes displayed a similar dose response in a MCF-7 cell line. Preliminary morphology studies with the three biologically active complexes in a HeLa cell line suggest that they induce cell death by apoptosis. Preliminary pBR322 plasmid DNA binding studies of selected [Pt(acylthioureato)Cl(RR'SO)]complexes clearly indicate that these complexes have a different mode of binding to DNA than cisplatin.
Keywords: Chemotherapy; Platinum